Identification and Expression Analysis of Fragaria Vesca MLO Genes Involved in Interaction with Powdery Mildew (Podosphaera Aphanis) - Shridhar, Jambagi; Jim, M. Dunwell (Journal of Advances in Plant Biology, 2017)
Strawberry powdery mildew, caused by Podosphaeraaphanis is a major fungal disease that affects strawberry yield and quality. In the model plant species Arabidopsis and the crop plants barley, tomato and pea, the Mildew resistance locus O (MLO) proteins have been found to be required for powdery mildew susceptibility. The present study, based on the sequence of a wild plum (Prunus americana) MLO protein, identified 16 MLO genes within the genome of woodland strawberry, Fragaria vesca and examined their expression pattern in response to powdery mildew infection in three diploid strawberry cultivars. Phylogenetic analysis showed that the FvMLO genes can be classified into six clades. Four FvMLO genes were grouped into clade III, which comprises MLO genes from Arabidopsis, tomato and grapevine that mediate powdery mildew susceptibility. A RNA-seq analysis of two diploid strawberry cultivars, F. vescassp. vesca accession Hawaii 4 (HW) and F. vesca f. semperflorens line “Yellow Wonder 5AF7” (YW) at 1 d (1 DAI) and 8 d (8 DAI) after infection showed the expression of 12 out of the 16 FvMLO genes. The comparison of Fragments Per Kilobase of transcript per Million mapped reads (FPKM values) detected by RNA-seq and expression values of qRT-PCR for FvMLO genes showed substantial agreement. The FvMLO3 gene, which was grouped in clade III and orthologous to the Arabidopsis,tomato and grapevine genes, was highly expressed in YW compared to other FvMLO genes across varieties. The results showed that FvMLO genes can be used as potential candidates to engineer powdery mildew resistance in strawberry based on MLO suppression or genome editing.
Keywords: Fragaria vesca; powdery mildew; FvMLO genes; gene expression; RNA-seq; qRT-PCR